Linking microbiome and hyperaccumulation in plants - Bočaj, Valentina (Acta biologica slovenica, 2025)
Hyperaccumulating plants can take up extraordinarily large concentrations of one or more metal(loid)s from the soil and accumulate it/them in the aboveground tissues without exibiting any visible toxicity symptoms. Among more than 700 plant taxa reported to have evolved this unique phenotype, the most common is the hyperaccumulation of nickel (Ni), and less common is the hyperaccumulation of arsenic (As), cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), manganese (Mn), lead (Pb), antimony (Sb), selenium (Se), thallium (Tl) or zinc (Zn). Metal(loid) hyperaccumulation is a result of several independent evolutionary events and despite considerable efforts, none of the proposed hypotheses on the environmental constraints driving these events has been supported fully to date. Among several tolerance strategies enabling hyperaccumulation is the allocation of metal(loid)s to competent cell types, typically away from photosynthetic apparatus, to limit damage to plant metabolism. Recently, the involvement of microorganisms colonizing roots in hyperacumulation phenomenon has achieved increased attention due to their role in the mobilization of metal(loid)s in the soil. The complex interactions between hyperaccumulation and belowground microbiome are of primary interest for phytoremediation, a promising green technology for removing or immobilisation of metal(loid)s in the soil with the help of plants. In this review, we discuss and complement current reports on the contribution of microorganisms to metal(loid) hyperaccumulation.
Keywords: arbuscular mycorrhizal fungi; arbuskularne mikorizne glive; dark septate endophytes; hiperakumulacija; hiperakumulacijske vrste; hyperaccumulating plants; hyperaccumulation; Kovine; Polkovine; rastlinski mikrobiom; temni septirani endofiti